PEMBINAAN TERHADAP NARAPIDANA DENGAN HUKUMAN SEUMUR HIDUP: STUDI KASUS DI LAPAS KELAS IIA PEKANBARU - Rahmadani, Dwi Putri; Rinaldi, Kasmanto (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The aim of this research is to describe the guidance of prisoners in the Indonesian criminal justice system, especially the guidance of prisoners with life sentences who are vulnerable to various disorders, including psychological disorders. The research method used is qualitative research, then data analysis is carried out by arranging, sorting, grouping and categorizing it according to the research context. The research results show the need for a holistic rehabilitative approach that involves various aspects, such as education, skills and mental health. Effective coaching not only improves individuals personally but also contributes to the prevention of reoffending and social reintegration. The implications of these findings for criminal policy and the justice system are also discussed